OCCURRENCE OF ATTINI (FORMICIDAE) IN TWO GEOMORPHOLOGICAL PROVINCES OF RIO GRANDE DO SUL, BRAZIL - Diehl, Elena; Diehl-Fleig, Eduardo; Albuquerque, EmÃlia Zoppas (REVISTA DE AGRICULTURA, 2017)
This paper deals with the occurrence of Attini (Hymenoptera, Formicidae) in two geomorphological regions of the Rio Grande do Sul State, Brazil The ant collections were made in 65counties of the Taquari Valley (Central Depression) and in 75 counties of the North Littoral (Coastal Plain), from1994 to 1997. Of the Myrmicinae we collected only the upper Attini. Seventeen (17) species of the Attinisubtribewere found, being one of the genus Atta and 16 of Acromyrmex. This number represents 70.83% of the leaf-cutting ants in the state, and 21.52% of the known species. The more frequent leaf-cutting ant was Atta sexdens, but it was not found in the Coastal Plain.Â  Of the Acromyrmex genus 16 species were collected in the two biogeographic regions but not all species were found in the same region, as well as frequencies differed from county to county. Not either one of the recorded species is endemic to one state region, but the recordings provided increased knowledge on the species geographical distribution.